If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4x = (-1x) + 6 Combine like terms: 5x + -4x = 1x 1x = (-1x) + 6 Reorder the terms: 1x = 6 + (-1x) Solving 1x = 6 + (-1x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(x)' to each side of the equation. 1x + (x) = 6 + (-1x) + (x) 1x + x = 6 + (-1x) + (x) Combine like terms: 1x + x = 2x 2x = 6 + (-1x) + (x) 2x = 6 + (-1x) + x Combine like terms: (-1x) + x = 0 2x = 6 + 0 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| X-2+7=10 | | 257-63x=0 | | 12s=(-36)+6s | | -5-8(2k-7)=115 | | k-4.3=-1.2 | | -1.4x+6=2.3x+28 | | 8x^2-4x=-9 | | -8(7x-4)=424 | | -3(3y-7)=21-9y | | -6=x-8-4 | | x+4=y | | 2x=(-30)+5x | | 23=-4n-7-6n | | 2(2x-x)=2x-1 | | 5b-6-7b+2=2 | | -18=n-3 | | 8x-10=(-2)-20 | | 14=n+n | | 8x-10=-2-20 | | -6y-4+3y-8=24 | | 4-8x+5x=-2 | | 2x^3+x^2-5x+2=-2 | | 4x+5y+20=0 | | x+3+8x=-15 | | 9x^2-18x+17=0 | | 8x+9-3x=8+5x+1 | | y-3=2y-7 | | -0.4x+0.7=4.3 | | x^2-4+24= | | X^2+10x+30=6 | | 8y=26-26 | | 9x+8=9+8x |